Triamcinolone acetonide and anecortave acetate do not stimulate uveal melanoma cell growth - el Filali, Mariam (Molecular Vision, 2008)
PURPOSE: Radiotherapy-induced radiation retinopathy can develop in over 40% of eyes treated for uveal melanoma. Triamcinolone acetonide (TA) and anecortave acetate (AA) can be used to treat radiation retinopathy. It is not known whether TA or AA has any effect on potentially still viable uveal melanoma cells in the choroid after radiotherapy. We therefore studied the effect of these drugs on the proliferation of uveal melanoma cell lines in vitro. Furthermore, as these drugs are supposed to counteract vascular leakage, we determined their effect on the expression and production of the proangiogenic vascular endothelial growth factor-A (VEGF-A), the antiangiogenic pigment epithelium-derived factor (PEDF), and thrombospondin-1 (TSP-1) in uveal melanoma cells. METHODS: Three uveal melanoma cell lines were treated in vitro with TA or AA. Cell proliferation was measured by counting cells and using the Water-Soluble Tetrazolium Salt-1 (WST-1) assay. VEGF-A and PEDF production was measured by ELISA, and intracellular expression of angiogenic-associated genes including VEGF-A, PEDF, and TSP-1 was determined by real-time quantitative RT–PCR. RESULTS: We found no effect of TA or AA on tumor cell growth or production of VEGF-A and PEDF in any of the three uveal melanoma cell lines tested. Regarding expression as measured by RT–PCR, TA had an inhibiting effect on TSP-1 in only one cell line, and no effect on VEGF-A or PEDF. AA showed a similar lack of effect. CONCLUSIONS: Since TA and AA do not stimulate uveal melanoma cell growth, it seems to be safe to use these drugs to treat radiation retinopathy after irradiation for uveal melanoma. Additional experiments using more cell lines or primary tumor cell cultures are needed to validate this conclusion. Furthermore, the results of our study suggest that TA does not exert its antileakage effect through downregulation of VEGF-A or upregulation of TSP-1 or PEDF in uveal melanoma cell lines. It is possible that TA and AA influence these pro- and antiangiogenic factors only under hypoxic circumstances. Further investigation is needed.